Analisa Efektivitas Mesin Paletizer dengan Metode OEE dan FMEA - Wahyudi, Muhammad; Soedarmadji, Wisma (LPPM Universitas Madako Tolitoli, 2025)
The manufacturing industry demands high production machine effectiveness to ensure smooth operations and maintain competitiveness. Issues related to machine effectiveness also occur at PT Tirta Fresindo Jaya, where the Palletizer machine recorded the highest downtime of 0.21%, compared to other production machines, indicating the need for a comprehensive performance evaluation. This study aims to analyze the effectiveness of the Palletizer machine using the Overall Equipment Effectiveness (OEE) method and to identify potential failures through Failure Mode and Effect Analysis (FMEA). A quantitative approach was employed in this research, with primary data collected through direct observation and recording of machine operational variables, while secondary data were obtained from production reports and company maintenance records. The OEE analysis was conducted based on three main parameters: availability, performance, and quality rate, whereas FMEA was applied to identify failure modes using the Risk Priority Number (RPN) as the assessment indicator. The results reveal that the OEE value of the Palletizer machine ranged between 84.42% and 90.10%, with both availability and quality rate meeting international standards, while performance remained below the world-class OEE benchmark. The Six Big Losses analysis indicated that the largest loss was caused by equipment failure, contributing 1.72% of the total downtime. Furthermore, the FMEA results showed that the sleding conveyor had the highest RPN value (343), followed by the push box and hydraulic pallet (336). Based on these findings, improvement efforts are recommended to focus on preventive maintenance of the sleding motor, scheduled replacement of hydraulic components, and routine inspections of the push box to minimize failure risks. Therefore, the integration of OEE and FMEA not only evaluates machine effectiveness but also provides strategic recommendations to reduce downtime and enhance sustainable productivity